New data on Phycosoma (Theridiidae, Hadrotarsinae) from China - Liu, Yang; Liang, Yun; Yin, Haiqiang; Xu, Xiang (Zootaxa, 2026)
The genus Phycosoma O. Pickard-Cambridge, 1880 (Hadrotarsinae Thorell, 1881, Theridiidae) has a cosmopolitan distribution. Over the past three decades, more than 20 species have been transferred to Phycosoma from Dipoena Thorell, 1869, 16 of which are from China. Consequently, the present study continues to focus on both genera, aiming to morphologically revise those Chinese species currently placed in Dipoena but requiring transfer to Phycosoma. In this study, a new species of Phycosoma is described from Yunnan, China: P. spinula sp. nov. (♂♀). In addition, three new combinations are proposed, all transferred from the genus Dipoena: P. gui (Zhu, 1998) comb. nov., P. linzhiense (Hu, 2001) comb. nov. and P. redunca (Zhu, 1998) comb. nov.. Upon completion of this study, no Chinese species currently assigned to Dipoena are considered to require transfer to Phycosoma. Detailed descriptions, morphological photos of the new species, and a distribution map of four Phycosoma species involved in this study are provided.